Climate-smart agriculture: what it's all about - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Why do we need climate-smart agriculture? And what do climate-smart farming practices look like? Meet some of the farmers who are leading the way! Learn more at https://ccafs.cgiar.org/climatesmart